2020
DOI: 10.1186/s43055-020-00172-8
|View full text |Cite
|
Sign up to set email alerts
|

Sonographic and Doppler predictors of malignancy in ovarian lesions

Abstract: Background: To determine the best sonographic (US) and/or Doppler features that the radiologist can use as predictors or risk factors for ovarian malignancy Results: Among the examined 156 ovarian lesions, there were 53 malignant and 103 benign lesions. Most of the malignant ovarian lesions were noted in older age than in benign lesions p < 0.001. Majority of the malignant lesions had non-hyperechoic solid component (92.5%); it had the highest sensitivity of 92.5%, specificity of 97%, accuracy of 94.8%, positi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 22 publications
3
1
0
Order By: Relevance
“…On adding doppler ndings, 72.8% were characterised as benign and 27.2% as [5] malignant. This was comparable with the studies done by Garg et al in [6] 2017 and Khalaf et al in 2018.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…On adding doppler ndings, 72.8% were characterised as benign and 27.2% as [5] malignant. This was comparable with the studies done by Garg et al in [6] 2017 and Khalaf et al in 2018.…”
Section: Resultssupporting
confidence: 92%
“…Among cystic and mixed lesions, thick septations, papillary projections and solid components were found in 22%, 34% and 33% cases respectively. This was comparable with the observation made by [6] Khalaf et al in 2018, where thick septations, papillary projections and solid components were observed respectively in 20%, 32.7% and 36.6% of their cases. The solid lesions in our study were well-dened, heterogeneous with foci of calcications and 1 showing necrosis.…”
Section: Resultssupporting
confidence: 92%
“…Previous studies have also shown that vascularized tissue, thick septations, and papillary projections were the most important and consistent ultrasound and Doppler predictors of ovarian malignancy [24,25]. Upon the analysis of our study population, the presence of papillae with blood flow and irregular cyst walls were significantly associated with a 20-fold and 10-fold increase in the likelihood of a malignant lesion.…”
Section: Discussionsupporting
confidence: 72%
“…Color doppler with spectral analysis such as PI and RI improves characterization of ovarian neoplasm by means of quantitative blood flow measurements obtained from tumor vessels. 10 It is the matter of the fact that low impedance to blood flow with high velocity is indicative of malignancy whereas moderate to high impedance to blood flow is suggestive of benign tumors. 92 % of malignant tumors in Taori Kb et al study showed blood flow; conversely absence of blood flow is equally important that suggest the benign nature of tumor.…”
Section: Discussionmentioning
confidence: 99%